Natural convection in a square cavity filled with a porous medium saturated with a nanofluid using the thermal nonequilibrium model with a Tiwari and Das nanofluid model; International Journal of Mechanical Sciences; Vol. 100 - Sheremet M. A. Mikhail Aleksandrovich (2015, 2015)
Title screen